5PSQ-076 Evaluation and monitoring of biochemical parameters in patients on parenteral nutrition. (23rd March 2022) - Pires, AM; Canário, C; Alcobia, A
Abstract : Background and importance: Nutritional support by the parenteral route aims to prevent and recover nutritional deficits whenever enteral nutrition is insufficient or contraindicated. Caloric requirements must be calculated according to the degree of metabolic stress, percentage of ideal weight and extent of intestinal failure. During parenteral nutrition (PN) complications such as hydroelectrolyte and metabolic imbalance may occur (eg, refeeding syndrome), which increase morbidity and mortality among patients. Aim and objectives: Monitoring the effectiveness of the protocol established in 2006 that provides for the PN onset within 72 hours with caloric restriction (in the first 24 hours starts with 50% of caloric needs, in 48 hours with 75%, and in 72 hours and following with 100%), as well as evaluating compliance with the recommendations of the American Society for Parenteral and Enteral Nutrition/European Society for Clinical Nutrition and Metabolism (ASPEN/ESPEN) PN guidelines. Material and methods: Retrospective analysis of biochemical parameters (albumin, total protein, C-reactive protein (CRP), serum creatinine (Cr), potassium, phosphate and magnesium) in patients with PN. Data were collected through the patient's clinical records and the calculation of nutritional needs was carried out using the Harris–Benedict formula. Results: Forty patients (14 women and 26 men) were analysed in the period April–August 2021 (age 72±12 years). The majority of patients were in Surgery Ward (78% patients). PN bags administered: 82% 1600 kcal, 13% 2200 kcal and 5% 1400 kcal. Gastric neoplasms and peritonitis were the main diagnoses associated with NP. The average onset of NP administration was 9±7 days. All patients showed high CRP (>5 mg/dL), low total protein (<6.6 g/dL) and 85% of patients showed hypoalbuminaemia at onset of PN. Although, daily analyses of the recommended electrolytes were not performed, it was observed that 20% developed hypokalaemia, 18% hypophosphataemia and 8% hypomagnesaemia. No refeeding syndrome was diagnosed in the studied sample. Conclusion and relevance: The start of 72-hour PN protocol with caloric restriction allowed avoidance of the refeeding syndrome, which usually appears within the first 7 days after the onset of PN. The compliance of ESPEN/ASPEN guidelines for daily monitoring of electrolytes was not observed for all patients. So, it will be proposed to reinforce pharmaceutical interventions, as well as developing together with the clinical team a monitoring protocol for patients under PN. References and/or acknowledgements: 1. ASPEN Consensus Recommendations for Refeeding Syndrome. Nutr Clin Pract 2020;35(6). doi : 10.1002/ncp.10474. Conflict of interest: No conflict of interest